Ethical controversies in abortion care, in vitro fertilization and contraception in women - Gutiérrez Ramos, Miguel (2023)
In relation to reproductive processes, the scientific evidence of recent years andthe vast and better information available for measuring and estimating morbidityand mortality indicators in reproductive health have led to the definition of newstrategies within the framework of women's right to health. For some peoplethese approaches are clear, but for others they are not so clear, generatingcontroversies in the light of ethical principles that need to be raised and, ifpossible, resolved. In this sense, we have selected for this presentation abortion,assisted reproduction and contraception, current issues that raise differentor opposing opinions of individuals or institutions, not always the product ofa reflection, fair, honest, non-ideologized, looking for the welfare of people.Sometimes, it is the result of the satisfaction of a personal or institutional interest.